A comparative study of oral health in three Late Bronze Age populations with different subsistence practices in North China. (16th June 2016) - Zhang, Hua; Merrett, Deborah C.; Xiao, Xiaoming; Zhang, Quanchao; Wei, Dong; Wang, Lixin; Ma, Xiaolin; Zhu, Hong; Yang, Dongya Y.
Abstract: This comparative study aims to examine dental lesions of three skeletal populations from Late Bronze Age North China to examine relationships between subsistence patterns and oral health in the past. The skeletal remains represent a unique series of ancient human populations who adopted different subsistence practices: Chenjiagou (ca. 3000–2200 BP) from Henan, Central China, representing an intensified agricultural practice; Houtaomuga (ca. 2250–2050 BP) from Jilin, Northeast China, representing hunting-gathering-fishing with limited mixed agriculture, Jinggouzi (ca. 2530–2440 BP) from Inner Mongolia of China, representing pastoral economy. The prevalences of dental caries, antemortem tooth loss, abscesses, and pulp chamber exposure were investigated in this study to examine potential connections between oral health and subsistance strategies. This study reveals that 1) overall, the worst oral health status was observed in the agriculturalists (Chenjiagou) when comparing with those of the mixed hunter-fisher-gatherers (Houtaomuga) and pastoralists (Jinggouzi); 2) dental pathological lesions (uncommon in subadults) were found to increase significantly with age in all three studied populations; 3) females were found to develop more severe dental lesions than males in all three sites, especially for the molars. This study demonstrates that high carbohydra dietary intake can significantly worsen oral health, which is consistent with observations from many other parts of the world. More studies are needed to investigate the causes of sex differences in severity of dental lesions between agriculturalists and non-agriculturalists.